Optical absorption and electronic spectra of chlorophylls a and b12. Issue 111 (17th November 2016) - Hedayatifar, Leila; Irani, Elnaz; Mazarei, Mahmood; Rasti, Soroush; Azar, Yavar T.; Rezakhani, Ali T.; Mashaghi, Alireza; Shayeganfar, Farzaneh; Anvari, Mehrnaz; Heydari, Tiam; Tabar, Ali Rahimi; Nafari, Nasser; et al.
Abstract : We report optical and electronic properties of the two main chlorophylls in green plants, namely, chlorophylls a and b. We estimate the electric moments of these molecules and study absorption spectra of the chlorophylls. Abstract : Photosynthesis includes capturing sunlight by an assembly of molecules, called chlorophylls, and directing the harvested energy in the form of electronic excitations to the reaction center. Here we report, using real-space density functional theory and time-dependent density functional theory together with GW calculations, the optical and electronic properties of the two main chlorophylls in green plants, namely, chlorophylls a and b. Furthermore, we estimate the dipole and primitive quadrupole electric moments of these molecules. We employ Casida's assignment ansatz to study the absorption spectra of the chlorophylls in the two main red and blue regions at various environments with different exchange–correlation functionals. In addition, we obtain the band gap of chlorophylls a and b, which are all in remarkable agreement with experimental observations.